Women's work in the military sector and its impact on family relations – A descriptive study on a sample of families in Jeddah - Al-Zahrani, Reem Abdulrahman; Al-Rami, Ramiyah Khader; El-Maghribi, Samira SaadElDin (Journal of Humanities & Social Sciences, 2025)
The work of women in the military sector has an impact on the family in general and on family relations in particular, so the study aimed to identify the extent of the impact of women's work in the military sector on family relations in Saudi society, which is represented in her relationship with her parents, brothers and relatives, and the study was applied to an intended sample  The number reached (62) female workers in the border guard and maritime sectors in Jeddah. The study used the descriptive approach, and the questionnaire was the data collection tool. By analyzing the study data, the following results emerged: The average of the “relationship with parents” axis for the study sample answers is equal to 2.182 This indicates that the study sample unanimously agreed that they "to some extent agree" ، and the average axis of “relationship with brothers” for the answers of the study sample is equal to 2.4401, and this indicates that the study sample unanimously agreed that they “agree”  , as the results of the study showed that the average of the “relationship with relatives” axis for the answers of the study sample is 1.7323, and this indicates that the study sample unanimously agreed that they “to some extent agree”).
Keywords: women's work; family relations; military action